2010
DOI: 10.1097/psy.0b013e3181cdbfc0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Impact of Mood on Flow-Mediated Dilation

Abstract: Objective To examine the impact of mood states on endothelial function, as measured noninvasively by brachial artery flow-mediated dilation (FMD). Substantial literature indicates that negative mood is linked to cardiovascular disease (CVD). However, the mechanisms underlying this relationship are not well defined. CVD is often preceded by dysfunction of the endothelium. Methods Healthy adults (n = 70; mean age, 36 years) completed the Profile of Mood States (POMS), which contains six subscales (depression/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
1
43
0
3
Order By: Relevance
“…Previous research demonstrated that depression is an independent risk factor for cardiovascular events, and that depressive mood is associated with adverse cardiovascular outcomes. 11,13,31 In line with recent findings by Cooper et al 16 our results suggest that although the subjects were not clinically depressed, even higher scores on a scale of depression may be a cardiovascular health risk. There is clinical evidence supporting the use of behavioral 32 and pharmacological interventions targeting depression to improve cardiovascular prognosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research demonstrated that depression is an independent risk factor for cardiovascular events, and that depressive mood is associated with adverse cardiovascular outcomes. 11,13,31 In line with recent findings by Cooper et al 16 our results suggest that although the subjects were not clinically depressed, even higher scores on a scale of depression may be a cardiovascular health risk. There is clinical evidence supporting the use of behavioral 32 and pharmacological interventions targeting depression to improve cardiovascular prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…15 Furthermore, recent findings demonstrate that even mild levels of adverse psychological states such as depression, anxiety and hostility may be linked to increased cardiovascular risk via impaired vasodilation. 16 Only one paper has examined the relationship between personality and MSBP. We previously reported that individual differences in hostility were related to different patterns of BP during sleep and the early morning hours in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that included women suggest an association between endothelial dysfunction and several cardiovascular risk factors. [7][8][9] The prevalence of SAH progressively increases with age, and this process occurs in women, especially at the beginning of the post-menopausal stage. These factors increase oxidative stress, compromising endothelial cells -this initial compromise is only functional, caused by the local inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,36 Previous studies examined FMD in women with premenstrual syndrome (PMS) 37 or healthy women in the postpartum 38 but did not assess the impact of SSRI treatment.…”
Section: Discussionmentioning
confidence: 99%